WSIA: web ontological search engine based on smart agents applied to scientific articles (2019)
The Semantic Web proposed by the W3C (Word Wide Web Consortium), aims to make the automation of the information contained in the current web through semantic processing based on ontologies that define what must be the rules used for the representation knowledge. This article resulting from the research project “Model for the representation of knowledge based on Web ontologies and intelligent search agents, if required: Scientific articles WSIA” proposes an architecture for finding information through intelligent agents and ontologies Web of scientific articles. This paper shows the architecture, implementation and comparing these with traditional applications.